Common factors in credit defaults swaps markets - Yi-hsuan Chen; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
We examine what are common factors that determine systematic credit risk and estimate and interpret the common risk factors. We also compare the contributions of common factors in explaining the changes of credit default swap (CDS) spreads during the pre-crisis, crisis and post-crisis period. Based on the testing result from the common principal components model, this study finds that the eigenstructures across the three subperiods are distinct and the determinants of risk factors differ from three subperiods. Furthermore, we analyze the predictive ability of dynamics in CDS indices changes by dynamic factor models.
Keywords: C38; G32; E43; 330; credit default swaps; common factors; credit risk; Kreditderivat; Kreditrisiko; Risikoprämie; Hauptkomponentenanalyse; Schätzung; Finanzkrise; Welt